ENTREPRENEURIAL CAPACITY BUILDING AMONG WOMEN-HEADED HOUSEHOLDS : AN INTEGRATED FRAMEWORK OF SELF-RELIANCE, CREATIVITY, AND ENTREPRENEURSHIP TRAINING IN JAMBI CITY - Isnaeni, Nurida; Indrawijaya, Sigit; Lubis, Paulina (Jurnal Manajemen Terapan dan Keuangan, 2026)
Abstract The rising number of Women-Headed Households in Indonesia has intensified household economic vulnerability, positioning entrepreneurship as a critical survival and empowerment strategy. However, the psychological mechanisms through which entrepreneurial intention is formed among economically vulnerable groups remain underexamined, as most evidence derives from student and general-enterprise populations. This study reconceptualizes entrepreneurship training as a capacity-building mechanism and examines how creativity and self-reliance shape entrepreneurial intention among Women-Headed Households in Jambi City. Grounded in Self-Determination Theory and interpreted through the Capability Approach, the study integrates creativity, self-reliance, entrepreneurial intention, and entrepreneurship training into a single explanatory model. A quantitative approach was applied, with data collected from 38 members of the SABDA community through stratified random sampling and analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS) in SmartPLS 4.0. The findings reveal that self-reliance exerts a positive and significant effect on both entrepreneurial intention and entrepreneurship training participation, and that entrepreneurial intention significantly strengthens training participation. In contrast, creativity shows a positive but statistically insignificant effect on both outcomes. These results indicate that within vulnerable populations, agentic capacity anchored in self-reliance is a more decisive driver of entrepreneurial readiness than ideational capacity anchored in creativity. The study contributes a capacity-building perspective to entrepreneurial-intention research, extends Self-Determination Theory to the context of vulnerable-group empowerment, and offers policy guidance for designing empowerment programs that prioritize the cultivation of autonomy and agency. Keywords: Entrepreneurial Capacity Building; Creativity; Self-Reliance; Entrepreneurship Training; Entrepreneurial Intention; Women-Headed Households